NPY and VGF Immunoreactivity Increased in the Arcuate Nucleus, but Decreased in the Nucleus of the Tractus Solitarius, of Type-II Diabetic Patients - Saderi, Nadia (Public Library of Science, 2012)
Ample animal studies demonstrate that neuropeptides NPY and α-MSH expressed in Arcuate Nucleus and Nucleus of the Tractus Solitarius, modulate glucose homeostasis and food intake. In contrast is the absence of data validating these observations for human disease. Here we compare the post mortem immunoreactivity of the metabolic neuropeptides NPY, αMSH and VGF in the infundibular nucleus, and brainstem of 11 type-2 diabetic and 11 non-diabetic individuals. α-MSH, NPY and tyrosine hydroxylase in human brain are localized in the same areas as in rodent brain. The similar distribution of NPY, α-MSH and VGF indicated that these neurons in the human brain may share similar functionality as in the rodent brain. The number of NPY and VGF immuno positive cells was increased in the infundibular nucleus of diabetic subjects in comparison to non-diabetic controls. In contrast, NPY and VGF were down regulated in the Nucleus of the Tractus Solitarius of diabetic patients. These results suggest an activation of NPY producing neurons in the arcuate nucleus, which, according to animal experimental studies, is related to a catabolic state and might be the basis for increased hepatic glucose production in type-2 diabetes.